2019
DOI: 10.1021/acs.orglett.8b03947
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Chemoselective Deprotection of Primary Acetates by Zirconium Hydrides

Abstract: A combination of DIBAL-H and Cp 2 ZrCl 2 is shown to promote the regioselective cleavage of primary acetates on a broad scope of substrates, ranging from carbohydrates to terpene derivatives, with a high tolerance toward protecting groups and numerous functionalities found in natural products and bioactive compounds. Apart from providing highly valuable building blocks in only two steps from biosourced raw materials, this selective de-O-acetylation should also be strongly helpful to solve selectivity issues in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 46 publications
(21 reference statements)
0
32
0
Order By: Relevance
“…These transformations can indeed be achieved with remarkable chemoselectivity, and involve intermediates having a versatile reactivity. , However, to the best of our knowledge, the reduction of CO bonds by zirconium hydrides has never been achieved with the main group metal hydride used as the stoichiometric reductant and a catalytic amount of zirconium complex . In this context, we recently reported that a mixture of Cp 2 ZrCl 2 and DIBAL-H in tetrahydrofuran (THF) induce the selective de- O -acetylation of the primary position of peracetylated compounds on a broad scope of polyfunctional substrates (Scheme a) . Schwartz’s reagent Cp 2 ZrHCl, which was initially believed to be formed in situ under our conditions, was eventually discarded as the reductive species.…”
Section: Introductionmentioning
confidence: 86%
“…These transformations can indeed be achieved with remarkable chemoselectivity, and involve intermediates having a versatile reactivity. , However, to the best of our knowledge, the reduction of CO bonds by zirconium hydrides has never been achieved with the main group metal hydride used as the stoichiometric reductant and a catalytic amount of zirconium complex . In this context, we recently reported that a mixture of Cp 2 ZrCl 2 and DIBAL-H in tetrahydrofuran (THF) induce the selective de- O -acetylation of the primary position of peracetylated compounds on a broad scope of polyfunctional substrates (Scheme a) . Schwartz’s reagent Cp 2 ZrHCl, which was initially believed to be formed in situ under our conditions, was eventually discarded as the reductive species.…”
Section: Introductionmentioning
confidence: 86%
“…In order to install a carbene precursor at position 6 on polyacetylated methyl αand βglucopyranosidic scaffolds, the primary alcohols 3 and 4 were first prepared by site-selective de-O-acetylation of 1 and 2 with DIBAL-H and Cp2ZrCl2 in THF, as recently reported by our group [14]. Bromoacetylation, followed by diazo transfer with TsNHNHTs and DBU in THF In the α-gluco series, decomposition of 5 with 2 mol% of Rh2(OAc)4 delivered a very complex mixture, from which two fractions could be isolated after careful chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…The conditions were however found to cleave benzyl ethers at the disaccharide level. Similarly, zirconium hydride has been proved to be effective reagent to selectively remove primary acetates in the presence of secondary ones …”
Section: New Reagents For Old Protecting Groupsmentioning
confidence: 99%
“…Similarly,z irconium hydride has been proved to be effective reagent to selectively removep rimary acetates in the presence of secondary ones. [48]…”
Section: New Reagentsfor Old Protectinggroupsmentioning
confidence: 99%